Studi Eksperimen Pengaruh Gelombang Dan Kecepatan Terhadap Pembentukan Tidal Flat Pantai Gambut - Genta Putra Adietama; Sigit Sutikno; Muhamad Yusa (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Tidal flat forms as the results of sedimentation processes which are mainly influenced by the coastal hydrodynamic. Tidal flat formation on the coastal peat is a unique phenomenon that has bee occurring at western part of Bengkalis Island, Riau Province, Indonesia. This study aimed to shed light some of aspect of its development. The method used in this research was laboratory test which simulate the tidal flat formation with five different wave variations. Simulations were carried out using coastal peat soil and seawater, collected from Meskom Village, Bengkalis Island, Riau Province, Indonesia. The equipment used in this simulation is a flume with a size of 500 cm x 25 cm x 7.6 cm, a wave generator, and a velocimeter. The results showed that tidal flat only formed as the result of small wave height i.e. 0.01 meters - 0.02 meters and a period between 1.43 seconds - 0.65 second, wave length of 0.149-1.25m and low current speed of 0.094-0.138m/s. Keywords: tidal flat, peat, wave, current